Market Transparency and Call Markets - Andreas Oehler; Matthias Unser (Otto-Friedrich-Universität Bamberg, Lehrstuhl für Betriebswirtschaftslehre, insbesondere Finanzwirtschaft, 1998)
This paper reports the results of 16 experimental asset markets that explore the effects of trade transparency on the price formation process and its results using a more realistic design than related studies. The open orderbook does not improve informational efficiency and does not result in higher liquidity (lower transaction costs). An increase in information intensity leads to both higher trading volume and higher volatility in both orderbook treatments. The comparison shows that they only differ in price volatility which is higher with an open orderbook. The market results mentioned above are confirmed by analyses on the individual level.
Keywords: G12; D44; G14; 330; Market Microstructure; Experimental Asset Markets; Orderbook Transparency; Individual Behavior in Call Markets; Börsenkurs; Volatilität; Börsenspiel; Informationseffizienz; Börsenumsatz; Mikrostrukturanalyse; Theorie